Individuality Incorporated : Indians and the Multicultural Modern - Pfister, Joel (Book collections on Project MUSE., 2004)
Joel Pfister examines how the US government has attempted over time to dictate to Native Americans how they should view their own individuality. He illustrates how concepts of individuality can be very different & how the federal blueprint for an 'Indian' falls far short of any objective reality.